A case study of ionospheric storm effects during long‐lasting southward IMF Bz‐driven geomagnetic storm - Liu, Jing (2014)
Multiple instrumental observations including GPS total electron content (TEC), foF2 and hmF2 from ionosondes, vertical ion drift measurements from Communication/Navigation Outage Forecasting System, magnetometer data, and far ultraviolet airglow measured by Thermosphere, Ionosphere, Mesosphere Energetics and Dynamics/Global Ultraviolet Imager (TIMED/GUVI) are used to investigate the profound ionospheric disturbances at midlatitude and low latitude during the 14–17 July 2012 geomagnetic storm event, which was featured by prolonged southward interplanetary geomagnetic field component for about 30 h below −10 nT. In the East Asian/Australian sector, latitudinal profile of TEC variations in the main phase were characterized by three bands of increments and separated by weak depressions in the equatorial ionospheric anomaly (EIA) crest regions, which were caused by the combined effects of disturbance dynamo electric fields (DDEF) and equatorward neutral winds. In the recovery phase, strong inhibition of EIA occurred and the summer crest of EIA disappeared on 16 July due to the combined effects of intrusion of neutral composition disturbance zone as shown by the TIMED/GUVI O/N2 measurements and long‐lasting daytime westward DDEF inferred from the equatorial electrojet observations. The transit time of DDEF over the dip equator from westward to eastward is around 2200 LT. In the American longitude, the salient ionospheric disturbances in the summer hemisphere were characterized by daytime periodical intrusion of negative phase for three consecutive days in the recovery phase, preceded by storm‐enhanced density plume in the initial phase. In addition, multiple short‐lived prompt penetration electric fields appeared during stable southward interplanetary magnetic field (IMF) Bz in the recovery phase and were responsible for enhanced the EIA and equatorial ionospheric uplift around sunset.